Hubungan Mekanisme Koping dengan Kualitas Hidup Remaja - Endang Sawitri; Esri Rusminingsih; Dewi Suryandari (TRIAGE Jurnal Ilmu Keperawatan, 2024)
Coping mechanisms are all efforts to manage stress, involving ways to solve problems using defense mechanisms to protect oneself. Effective coping mechanisms can help improve the quality of life. This study aims to examine the relationship between coping mechanisms and the quality of life among adolescents in Dukuh Pucung, Desa Kraguman. The research method uses a cross-sectional approach. This study employs total sampling with a sample size of 75 respondents. Data were collected using the Brief COPE Inventory (BCI) and the WHOQOL-BREF questionnaire. The analysis was performed using Kendall's tau test with a p-value of 0.05. The results showed that 77,3% adolescents used adaptive coping mechanisms, while 22,7% adolescents used maladaptive coping mechanisms. Additionally, 77,3% adolescents had a good quality of life, whereas 22,7% adolescents had a poor quality of life. Based on the Kendall's tau test analysis, a significance value (p) of 0.000 (α=0.05) was obtained. Therefore, it can be concluded that there is a relationship between coping mechanisms and the quality of life among adolescents in Dukuh Pucung, Desa Kraguman